2011
DOI: 10.1519/jsc.0b013e318212db21
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Carbohydrate–Protein Supplementation Improves Subsequent Exercise Performance and Intracellular Signaling for Protein Synthesis

Abstract: Postexercise carbohydrate-protein (CHO + PRO) supplementation has been proposed to improve recovery and subsequent endurance performance compared to CHO supplementation. This study compared the effects of a CHO + PRO supplement in the form of chocolate milk (CM), isocaloric CHO, and placebo (PLA) on recovery and subsequent exercise performance. Ten cyclists performed 3 trials, cycling 1.5 hours at 70% VO₂max plus 10 minutes of intervals. They ingested supplements immediately postexercise and 2 hours into a 4-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 49 publications
4
71
1
Order By: Relevance
“…In the recovery period we found that a single bout of exercise significantly increased postexercise muscle protein breakdown in patients with DM1, FSHD, BMD, and LGMD2I during the first 3 h of recovery, which contrasted findings in healthy subjects, in whom there was a positive protein balance postexercise as earlier described (8,16). This seems to support the old notion that patients with muscular dystrophies should refrain from exercise training, because it can potentially damage muscle fibers and accelerate the disease process.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the recovery period we found that a single bout of exercise significantly increased postexercise muscle protein breakdown in patients with DM1, FSHD, BMD, and LGMD2I during the first 3 h of recovery, which contrasted findings in healthy subjects, in whom there was a positive protein balance postexercise as earlier described (8,16). This seems to support the old notion that patients with muscular dystrophies should refrain from exercise training, because it can potentially damage muscle fibers and accelerate the disease process.…”
Section: Discussionsupporting
confidence: 83%
“…These encouraging findings of an anabolic effect of oral supplementation after endurance exercise are supported by a study using a comparable protocol, in which Murphy and Miller found an increased whole body protein turnover in elderly, healthy subjects (16). Furthermore, protein supplements after endurance exercise reduce muscle injuries and improve retest results after a recovery period in healthy individuals (8). A higher resynthesis of muscle glycogen and a greater protein synthesis signaling cascade activation were demonstrated after protein supplementation compared with both an isocaloric carbohydrate and a placebo supplementation (8).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We fi rst investigated the effects of chocolate milk, compared to carbohydrate and placebo, on recovery from an acute exercise bout and subsequent cycling time trial performance [ 156 ]. Ten trained cyclists rode a 90-min glycogen depletion ride, followed by a 4-h recovery period in the laboratory.…”
Section: Sidebarmentioning
confidence: 99%
“…We also found that the proteins that control protein synthesis were activated to a greater extent after ingesting the chocolate milk beverage than the carbohydrate or placebo. Therefore, chocolate milk was shown to be a highly effective recovery supplement when ingested immediately and 2 h post-exercise [ 156 ]. From these results, we hypothesized that if chocolate milk were ingested post-exercise during an endurance training program, training adaptations would be signifi cantly greater than if supplementing with carbohydrate only or nothing at all after each workout.…”
Section: Sidebarmentioning
confidence: 99%